Unit commitment direct current optimal power flow using mixed-integer linear programming. Issue 1 (July 2020) - Azis, M F; Habibuddin, J; Mutmainnah,; Muchtar, T; Purwanto, D
Abstract: This paper presents unit commitment direct current optimal power flow (UCDCOPF) using mixed-integer linear programming (MILP) for daily power system generation planning. This method is used to solve optimum operation in an electric power system by scheduling generator status and calculating the optimal power output of each generator in a power system. The calculation of this method considers several constraints in the power system. A modified IEEE 24 bus system is used as a test system to show the ability of the proposed approach.